Associations between consumption of dietary fibers and the risk of cardiovascular diseases, cancers, type 2 diabetes, and mortality in the prospective NutriNet-Santé cohort. Issue 1 (5th May 2020) - Partula, Valentin; Deschasaux, Mélanie; Druesne-Pecollo, Nathalie; Latino-Martel, Paule; Desmetz, Elisa; Chazelas, Eloi; Kesse-Guyot, Emmanuelle; Julia, Chantal; Fezeu, Léopold K; Galan, Pilar; Hercberg, Serge; Mondot, Stanislas; et al.
ABSTRACT: Background: Mounting evidence, yet with varying levels of proof, suggests that dietary fibers (DFs) may exert a protective role against various chronic diseases, but this might depend on the DF type and source. Objectives: Our objectives were to assess the associations between the intake of DFs of different types [total (TDF), soluble (SF), insoluble (IF)] and from different sources (fruits, vegetables, whole grains, legumes, potatoes and tubers) and the risk of cardiovascular diseases (CVDs), cancer, type 2 diabetes (T2D), and mortality in the large-scale NutriNet-Santé prospective cohort (2009–2019). Methods: Overall, 107, 377 participants were included. Usual DF intake was estimated from validated repeated 24-h dietary records over the first 2 y following inclusion in the cohort. Associations between sex-specific quintiles of DF intake and the risk of chronic diseases and mortality were assessed using multiadjusted Cox proportional hazards models. Results: T2D risk was inversely associated with TDFs [HR for quintile 5 compared with quintile 1: 0.59 (95% CI: 0.42, 0.82), P -trend <0.001], SFs [HR: 0.77 (0.56, 1.08); P -trend = 0.02], and IFs [HR: 0.69 (0.50, 0.96); P -trend = 0.004]. SFs were associated with a decreased risk of CVD [HR: 0.80 (0.66, 0.98); P -trend = 0.01] and colorectal cancer [HR: 0.41 (0.21, 0.79); P -trend = 0.01]. IFs were inversely associated with mortality from cancer or CVDs [HR: 0.65 (0.45, 0.94); P -trend = 0.02]. TDF intake was associated with a decreased risk of breast cancer [HR:: 0.79 (0.54, 1.13); P -trend = 0.04]. DF intake from fruit was associated with the risk of several chronic diseases. Conclusions: Our results suggest that DF intake, especially SFs and DFs from fruits, was inversely associated with the risk of several chronic diseases and with mortality. Further studies are needed, involving different types and sources of fiber. Meanwhile, more emphasis should be put on DFs in public health nutrition policies, as DF intake remains below the recommended levels in many countries. This trial was registered at clinicaltrials.gov as NCT03335644.